Fish promote stronger functional changes in microcrustaceans than macroinvertebrates in artificially vegetated mesocosms in both subtropical and temperate lakes - Morari, Pedro Henrique Ribeiro [UNESP]; Dos Santos, Natan Guilherme [UNESP]; Iglesias, Carlos; Meerhoff, Mariana; Jeppesen, Erik; Castilho-Noll, Maria Stela Maioli [UNESP] (Springer Nature, 2025)
Predation by fish and macroinvertebrates may differentially shape the functional traits of microcrustaceans to avoid predation. To test this, we conducted a 49-day mesocosm experiment in shallow lakes in temperate (Denmark) and subtropical (Uruguay) regions. Treatments included (1) fish only, (2) macroinvertebrates only, (3) both predators, and (4) a control with no predators. Microcrustaceans were identified to species level and classified by functional traits (predator escape tactics, body size, and feeding strategy), with data analyzed using generalized linear mixed models. Fish predation strongly targeted large, rapid swimming microcrustaceans, with significant differences in density between treatments containing fish (alone or combined with macroinvertebrates) and the control and macroinvertebrate-only treatments. Contrary to predictions and previous studies, macroinvertebrates showed minimal effects on microcrustacean functional traits, even in warmer systems. We conclude that fish play a dominant role in structuring microcrustacean functional diversity compared to macroinvertebrates, although further experimental validation is needed to generalize these findings.